Recent advances in the genome-wide study of DNA replication origins in yeast - Peng, Chong; Luo, Hao; Zhang, Xi; Gao, Feng (Frontiers in Microbiology, 2015)
DNA replication, one of the central events in the cell cycle, is the basis of biological inheritance. In order to be duplicated, a DNA double helix must be opened at defined sites, which are called DNA replication origins (ORIs). Unlike in bacteria, where replication initiates from a single replication origin, multiple origins are utilized in the eukaryotic genome. Among them, the ORIs in budding yeast Saccharomyces cerevisiae and the fission yeast Schizosaccharomyces pombe have been best characterized. In recent years, advances in DNA microarray and next-generation sequencing technologies have increased the number of yeast species involved in ORIs research dramatically. The ORIs in some nonconventional yeast species such as Kluyveromyces lactis and Pichia pastoris have also been genome-widely identified. Relevant databases of replication origins in yeast were constructed, then the comparative genomic analysis can be carried out. Here, we review several experimental approaches that have been used to map replication origins in yeast and some of the available web resources related to yeast ORIs. We also discuss the sequence characteristics and chromosome structures of ORIs in the four yeast species, which can be utilized to improve the replication origins prediction.